2018
DOI: 10.1039/c8nr90093k
|View full text |Cite
|
Sign up to set email alerts
|

Correction: A computational exploration of the crystal energy and charge-carrier mobility landscapes of the chiral [6]helicene molecule

Abstract: Correction for 'A computational exploration of the crystal energy and charge-carrier mobility landscapes of the chiral [6]helicene molecule' by Beth Rice et al., Nanoscale, 2018, 10, 1865-1876.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…In TES‐Pn, J max is equal to J max in 16 ; the lower hole mobility is largely related to a higher λ ( λ inner =142 meV). The maximum hole mobility of 3.75 cm 2 V −1 s −1 in 16 exceeds all hole mobilities for helicenes previously computed (i) aza[6]helicene regioisomers ( λ outer =0.30 eV) 0.02–0.26 cm 2 V −1 s −1 ; [27] (ii) carbo[6]helicene ( λ outer =0.14 eV) 0.00–2.00 cm 2 V −1 s −1 ; [11b,c] (iii) (rac)‐aza[6]helicene 0.06 cm 2 V −1 s −1 and (+)‐aza[6]helicene 0.03 cm 2 V −1 s −1 [11a] . Those helicenes generally show smaller hole transfer integrals and larger λ intra (hole) as would be expected for smaller molecules.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In TES‐Pn, J max is equal to J max in 16 ; the lower hole mobility is largely related to a higher λ ( λ inner =142 meV). The maximum hole mobility of 3.75 cm 2 V −1 s −1 in 16 exceeds all hole mobilities for helicenes previously computed (i) aza[6]helicene regioisomers ( λ outer =0.30 eV) 0.02–0.26 cm 2 V −1 s −1 ; [27] (ii) carbo[6]helicene ( λ outer =0.14 eV) 0.00–2.00 cm 2 V −1 s −1 ; [11b,c] (iii) (rac)‐aza[6]helicene 0.06 cm 2 V −1 s −1 and (+)‐aza[6]helicene 0.03 cm 2 V −1 s −1 [11a] . Those helicenes generally show smaller hole transfer integrals and larger λ intra (hole) as would be expected for smaller molecules.…”
Section: Resultsmentioning
confidence: 53%
“…[8] Spin-filtering properties of chiral compounds,k nown as the chirality induced spin selectivity effect (CISS-effect), [9] render helicenes intriguing targets for spin dependent applications [10] like spintronics.F inally,h elicity is au seful tool to fine-tune the parameters for organic materials,asmixtures of enantiomers in different ratios lead to varying solid-state packings and, therefore,d ifferent properties. [11] Form any of these purposes,such as optical and electronic applications,the p-extension of helicenes is beneficial due to the strong visible light absorption and fluorescence,t unable semiconducting properties,and aggregation of large p-systems.…”
Section: Introductionmentioning
confidence: 99%
“…In TES‐Pn, J max is equal to J max in 16 ; the lower hole mobility is largely related to a higher λ ( λ inner =142 meV). The maximum hole mobility of 3.75 cm 2 V −1 s −1 in 16 exceeds all hole mobilities for helicenes previously computed (i) aza[6]helicene regioisomers ( λ outer =0.30 eV) 0.02–0.26 cm 2 V −1 s −1 ; [27] (ii) carbo[6]helicene ( λ outer =0.14 eV) 0.00–2.00 cm 2 V −1 s −1 ;[ 11b , 11c ] (iii) (rac)‐aza[6]helicene 0.06 cm 2 V −1 s −1 and (+)‐aza[6]helicene 0.03 cm 2 V −1 s −1 . [11a] Those helicenes generally show smaller hole transfer integrals and larger λ intra (hole) as would be expected for smaller molecules.…”
Section: Resultsmentioning
confidence: 59%
“…25 Previously, we performed CSP studies to predict the carbo [6]helicene and aza [6]helicene crystal-energy landscapes and found that the chirality of the crystal (enantiopure vs. racemic) can drastically affect the corresponding charge-carrier mobilities. 31,32 For carbo [6]helicene, we structurally classified polymorphs into recurring packing motifs. A particular 'translational motif' (Figure 1c) was found with the highest probability across the entire crystal-energy landscape, being observed in 63% of the hypothetical low-energy polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…A particular 'translational motif' (Figure 1c) was found with the highest probability across the entire crystal-energy landscape, being observed in 63% of the hypothetical low-energy polymorphs. 32 Most recently, Salerno et al studied the effect of the nitrogen substitution position on charge transport for the most commonly observed [6]helicene crystal structure (CSD code: HEXHEL, Figure 1b), 33 and found that this same 'translational motif' gave rise to the highest electron-transfer integrals across the majority of aza [6]helicene isomers.…”
Section: Introductionmentioning
confidence: 99%